Review: Physiologically functional components of mare's milk - A. Mazhitova; A. Kulmyrzaev (MANAS: Journal of Engineering, 2015)
Mare's milk popularity as a health-promoting food product is continuously increasing. The reason for this phenomenon is the historical traditions of the Kyrgyz people in use of mare milk for therapeutic purposes and scientifically based approaches in traditional medicine. The unique composition of mare's milk is the basis of all its health-promoting properties. It containing essential amino acids, vitamins C and E, and unsaturated fatty acids. Calcium and phosphorus content of mare’s milk is almost the same as in human milk. Also high content of lactoferrin, lysozyme, immunoglobulins provides to mare’s milk immunomodulatory, anti-carcinogenic, anti-viral properties.